The impact of children’s dental anxiety on dentists - V. A. Katyukhina; I. A. Nikolskaya; I. Yu. Gileva; L. A. Sokolov; A. S. Larina; D. F. Galiullina; S. Zh. Zhusupbekov (Эндодонтия Today)
INTRODUCTION. According to statistics, medical workers and, in particular, dentists are exposed to stressful factors in the workplace on a daily basis. Due to the specifics of their daily activities, pediatric dentists experience a great emotional burden, especially when treating children who are not adapted to dental care, which leads to the development of an emotional burnout syndrome among specialists. AIM. To determine the effect of children’s dental anxiety on emotional stability during admission and psychoemotional status after admission by dentists with emotional burnout syndrome.MATERIALS AND METHODS. The study involved 76 pediatric dentists and 68 patients aged 6–7 years. The psychoemotional state of dentists was assessed using the Maslach Burnout Questionnaire and a Visual Analog Scale. The behavior of children at the dental appointment was recorded according to the evaluation scale of the behavioral profile of the Melamed.RESULTS. According to the results of the Maslach questionnaire, burnout syndrome of varying severity was detected in all specialists. Deterioration of the psychoemotional state after receiving a patient who was not adapted to dental treatment was observed in 16%.CONCLUSIONS. The study shows that in order to prevent burnout syndrome in pediatric dentists, it is necessary to reduce professional stress through methods of adapting children to treatment, correcting patient behavior and reducing dental anxiety.